Internationalization and its challenges at U.S. regional comprehensive universities: The transformational leadership role of senior international officers - Yaro, Ibrahima F.; Hughey, Aaron W. (Journal of International Students, 2025)
This interpretive phenomenological analysis investigated the role of transformational leadership and the challenges that senior international officers (SIOs) face in internationalizing regional comprehensive universities (RCUs) in the United States. Twelve in-depth interviews were conducted with SIOs from five regions: the West, Midwest, South, Southeast, and Northwest. The findings indicate that the transformational leadership approach is the primary leadership style utilized by senior international officers for the effective and successful internationalization of their institutions. The findings highlight a wide range of challenges that a senior international officer may encounter at a regional comprehensive university in the United States. The study outlines implications for practice for aspiring SIOs and current senior leaders in the United States.